Spiders of Himachal Pradesh: A preliminary checklist - Das Sarkar, Irina; Uniyal, V.P.; Siliwal, Manju (Indian Forester, 2022)
The current paper presents the first comprehensive checklist of spider fauna occurring and/or reported from the western Himalayan state of Himachal Pradesh, as compiled from peer-reviewed published secondary literature sources. 59 species of spiders belonging to 10 families have been enlisted, which have been originally either described as state-specific records or type locality from Himachal Pradesh, of which a few have been subjected to taxonomic revisions. Of the 59 reported species, 18 species across 7 families remain reported only till the generic level, leaving an information blind-spot of them being re-reported across sources as unique species, highlighting the need to have a more systematic diversity database for this understudied faunal group.